The appropriateness of training exposures for match-play preparation in adolescent schoolboy and academy rugby union players. Issue 6 (19th March 2018) - Phibbs, Padraic J.; Jones, Ben; Read, Dale B.; Roe, Gregory A.B.; Darrall-Jones, Joshua; Weakley, Jonathon J.S.; Rock, Andrew; Till, Kevin
ABSTRACT: The aim of this study was to compare the physical and movement demands between training and match-play in schoolboy and academy adolescent rugby union (RU) players. Sixty-one adolescent male RU players (mean ± SD; age 17.0 ± 0.7 years) were recruited from four teams representing school and regional academy standards. Players were categorised into four groups based on playing standard and position: schoolboy forwards (n = 15), schoolboy backs (n = 15), academy forwards (n = 16) and academy backs (n = 15). Global positioning system and accelerometry measures were obtained from training and match-play to assess within-group differences between conditions. Maximum data were analysed from 79 match files across 8 matches (1.3 ± 0.5 matches per participant) and 152 training files across 15 training sessions (2.5 ± 0.5 training sessions per participant). Schoolboy forwards were underprepared for low-intensity activities experienced during match-play, with schoolboy backs underprepared for all movement demands. Academy forwards were exposed to similar physical demands in training to matches, with academy backs similar to or exceeding values for all measured variables. Schoolboy players were underprepared for many key, position-specific aspects of match-play, which could place them at greater risk of injury and hinder performance, unlike academy players who were better prepared.